2020
DOI: 10.1177/0009922820944400
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Clinic: A Novel Model to Provide Timely, Comprehensive Care to Newborns Following Nursery Discharge

Abstract: Ensuring safe and timely follow-up after well baby nursery (WBN) discharge is an ongoing challenge. This study demonstrates the efficacy of a novel model for follow-up, the Newborn Clinic (NBC), in reducing time to outpatient follow-up after WBN discharge. Our retrospective chart review of 17 952 newborns found that time to follow-up visit decreased significantly following NBC establishment. Emergency department visits, a marker of infant morbidity, were slightly increased in the post-establishment cohort. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Multiple studies have shown a decrease in LOS. 10,11 Given overall trends of decreasing LOS after surgical procedures, it was not surprising that LOS after the CS also significantly decreased. 12 We anticipated that a birth time before 2pm would increase the likelihood of an early discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown a decrease in LOS. 10,11 Given overall trends of decreasing LOS after surgical procedures, it was not surprising that LOS after the CS also significantly decreased. 12 We anticipated that a birth time before 2pm would increase the likelihood of an early discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown a decrease in LOS. 10 11 Given overall trends of decreasing LOS after surgical procedures, it was not surprising that LOS after the CS also significantly decreased. 12…”
Section: Discussionmentioning
confidence: 99%
“…The COVID Nursery Follow-Up Clinic was created by modifying an existing in-person Newborn Clinic framework and was physically located in our children's hospital separate from our hospital-affiliated, community-based primary care sites (4). Clinic personnel consisted of a front office staff person, a medical assistant, and 2 pediatricians dedicated to this clinic.…”
Section: Descriptionmentioning
confidence: 99%